Process Parameter Optimization in Finish Wire Electrical Discharge Machining of SUS420J2 Steel - Mai, Nguyen Trong; Trinh, Du Thi Kieu; Hung, Nguyen Viet (Engineering, Technology & Applied Science Research, 2026)
Wire Electrical Discharge Machining (WEDM) is a non-traditional manufacturing technique widely used in many industrial sectors. This study aims to identify the optimal settings for three key process parameters in the finishing process of SUS420J2 steel. A 15-trial experimental matrix was established using the Box-Behnken design and incorporating input variables such as peak current, voltage, and pulse-on time. Two output responses were evaluated for each trial: surface roughness and white layer thickness, applying a novel computational framework, Method based on the Removal Effects of Criteria - Rank Order Centroid (MEREC-ROC), to determine the relative importance. The Generalized Reduced Gradient (GRG) algorithm was applied to address the multi-objective optimization challenge, with peak current, voltage, and pulse-on time being measured at 1.94 A, 79.6 V, and 6.96 μs, respectively. Under these conditions, surface roughness and white layer thickness simultaneously reached their minimum levels, at 1.262 μm and 4.828 μm, respectively. Furthermore, this study analyzes in depth the degree to which each process parameter influences the resulting responses.